Use of infant donor tissue in endothelial keratoplasty - Moshirfar M (Dove Medical Press, 2015)
Majid Moshirfar,1 Yichieh Shiuey,2 Carlton Robert Fenzl3 1Department of Ophthalmology, Francis I Proctor Foundation, University of California San Francisco, San Francisco, CA, USA; 2Palo Alto Medical Foundation, Sunnyvale, CA, USA; 3John A Moran Eye Center, University of Utah, Salt Lake City, UT, USA We have read with great interest the recent article by Kobayashi et al describing endothelial keratoplasty using infant donor tissue.1 This is a fine case report describing the use of infant donor tissue as a viable source when performing non-Descemet stripping automated endothelial keratoplasty (nDSAEK). Descemet stripping automated endothelial keratoplasty (DSAEK) and nDSAEK seem to be the only currently accepted forms of keratoplasty for which donor tissue under the age of 2 years is acceptable. When used to perform penetrating keratoplasty, it is known that infantile grafts behave in an ectatic fashion.2,3 This is likely due to their more elastic properties. Tissue preparation in Descemet membrane endothelial keratoplasty (DMEK) proves to be too difficult given the strength of adhesion of Descemet membrane to the overlying stroma.1 Read the original article